2007
DOI: 10.1002/macp.200790040
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Chem. Phys. 21/2007

Abstract: Front Cover: The cover illustrates a strategy for a simple preparation of the proton conductive composite membrane composed of poly(2,5-benzimidazole) and zirconium pyrophosphate via a PPA direct casting method. The SEM image shows the zirconium pyrophosphate particles in the composite membrane when the content of the zirconium pyrophosphate is about 30 wt.-%. Further details can be found in the article by T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…2). ABPBI has been studied by Litt et al, 61 Akita et al, 62 by our group, [63][64][65] Kim et al, 55, 66 Krishnan et al, 67 J.-H. Lee et al, 68,69 J.-C. Lee et al, 70,71 Wannek et al, 72,73 Corti et al 74,75 and Bozkurt, 76 doped with PA. All have found that ABPBI absorbs much more acid than PBI when treated with identical phosphoric acid solutions. Furthermore, ABPBI membranes have the same performance as PBI under the same conditions 60 and can be produced easily and more safely from a single cheap monomer.…”
Section: Alternative Pem Polymers Of the Benzimidazole Familymentioning
confidence: 99%
“…2). ABPBI has been studied by Litt et al, 61 Akita et al, 62 by our group, [63][64][65] Kim et al, 55, 66 Krishnan et al, 67 J.-H. Lee et al, 68,69 J.-C. Lee et al, 70,71 Wannek et al, 72,73 Corti et al 74,75 and Bozkurt, 76 doped with PA. All have found that ABPBI absorbs much more acid than PBI when treated with identical phosphoric acid solutions. Furthermore, ABPBI membranes have the same performance as PBI under the same conditions 60 and can be produced easily and more safely from a single cheap monomer.…”
Section: Alternative Pem Polymers Of the Benzimidazole Familymentioning
confidence: 99%
“…Poly(2,5-benzimidazole) (ABPBI) has a similar structure and properties to PBI-ph [21,22] , and the monomer system for ABPBI synthesis is much simpler and cheaper. However, compared to PBI-ph, ABPBI is hard to be dissolved except in the strong acid such as sulfuric acid, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] The effect of various amounts of LiHzS on the mechanical properties It is possible that the use of 10 wt.-% of LiHzS in the composite membrane produced some phase separated domains, resulting in poorer mechanical properties as reported previously. [17,27] Other mechanical properties of PBI-LiHzS2.5 and PBI-LiHzS5, such as elongation at break and Young's modulus, are also close to those of PBI. These mechanical properties indicate that the PBI-LiHzS composite membranes have good mechanical stability that is suitable for use in high-temperature fuel cell membranes.…”
Section: Resultsmentioning
confidence: 72%
“…[19][20][21][22][23][24][25][26] Furthermore, some of the PBI composite membranes showed higher mechanical stability in comparison to PBI membranes with the same acid content. The inorganic compounds used for the composite membranes include phosphotungstic acid (H 3 PW 12 O 40 Á nH 2 O), [20] zirconium phosphate [Zr(HPO 4 ) 2 Á nH 2 O], [20] zirconium pyrophosphate (ZrP 2 O 7 ), [27] silicotungstic acid (H 4 SiW 12 O 40 Á nH 2 O), [20] zirconium tricarboxybutylphosphonate {Zr[O 3 PC(CH 2 ) 3 (-COOH) 3 ] 2 }, [21] boron phosphate (BPO 4 ), [22] silica nanoparticles, [23,24,28] and Cs 2.5 H 0.5 PMo 12 O 40 . [25] Lithium hydrazinium sulfate (LiN 2 H 5 SO 4 , LiHzS) has been known as a proton-conducting solid.…”
Section: Introductionmentioning
confidence: 99%